Pengaruh Strategi Pemasaran Terhadap Minat Beli Pada Optik Permata - Rizky Ardhiansyah; Irfan Wildzan Muafa; Sopia Betaubun (Musamus Journal of Business & Management, 2022)
This study aims to find the influence of marketing strategy on buying interest at Optic Permata Merauke. The population in this study is people who have been or are visiting Optic Permata Merauke which is 211 people. The sample in this study amounted to 95 people with determination using Accidental Sampling method. The research approach used is a quantitative approach and uses simple linear regression analysis with SPSS version 26 tools. From the results of simple linear regression analysis that has been processed inobtain equation Y = 2,966 + 0,890 + e From the hypothetical test results, the t test shows that Marketing Strategy variables have a partial significant influence This is evidenced by the value t calculate Marketing Strategi (X) 16,579 > ttable 1,66140 with a significant rate of 0.000 < 0.05 so that Ha received H0 is rejected. R Square value is 0.747 which means that free variables affect consumer satisfaction Marketing Strategi of 74,7% while the remaining 25,3% is influenced by other variables that were not studied in this study.